Perceptions and Experiences of Women in Karachi, Pakistan Regarding Secondary Infertility: Results from a Community-Based Qualitative Study - Neelofar Sami; Tazeen Saeed Ali (Hindawi Limited, 2012)
Background. The prevalence of infertility in Pakistan is 22% with primary infertility at 4% and secondary infertility at 18%. This study explored perceptions and experiences of women in Karachi, Pakistan regarding the causes, treatment-seeking behavior for and consequences of secondary infertility. Methods. Focus group discussions and in-depth interviews with married women explored their perceptions and experiences for issues related to secondary infertility. Results. The knowledge of women about the causes and scientific treatment options for infertility was limited resulting in inclination for traditional unsafe health care. Infertility was stated to result in marital instability, stigmatization and abuse specially for women with no live child. Conclusions. Since infertility can have a serious effect on both the psychological well-being and the social status of women in Pakistan, effective interventions are the need of the day. There is a dire need for health education and counseling to be integrated into infertility management plans.